SPUTTERING TARGET MEMBER, SPUTTERING TARGET ASSEMBLY, AND FILM DEPOSITION METHOD
The Co-Cr-Pt sputtering target member, featuring a matrix phase and dispersed alloy particles with varying magnetic properties, addresses the challenges of stable leakage magnetic flux and nonmagnetic material aggregation, enhancing sputtering stability and target longevity.
Patent Information
- Application Number
- JP2021072129
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-04-21
AI Technical Summary
Existing sputtering targets for magnetic recording media face challenges in maintaining stable leakage magnetic flux and preventing the aggregation of nonmagnetic materials, which can lead to abnormal discharges and reduced target life.
A Co-Cr-Pt sputtering target member is developed with a matrix phase containing Co, Cr, Pt, and nonmagnetic materials, and a Co-Cr-Pt alloy particle phase dispersed within. The Co-Cr-Pt alloy particles have different magnetic properties than the matrix phase, enhancing leakage magnetic flux and slowing metal component diffusion to suppress nonmagnetic material aggregation.
The solution achieves improved leakage magnetic flux and reduced aggregation of nonmagnetic materials, resulting in stable sputtering operations, extended target life, and cost-effective production of magnetic thin films.
Smart Images

Figure 0007648429000008 
Figure 0007648429000009 
Figure 0007648429000010
Abstract
Description
[Technical field]
[0001] In one embodiment, the present invention relates to a Co-Cr-Pt-based sputtering target member suitable for manufacturing perpendicular magnetic recording media. In another embodiment, the present invention relates to a sputtering target assembly including such a sputtering target member. In yet another embodiment, the present invention relates to a film formation method using such a sputtering target member. [Background technology]
[0002] In the field of magnetic recording, as typified by hard disk drives, materials based on ferromagnetic metals Co, Fe, or Ni are used as materials for magnetic thin films that perform recording. For example, Co-Cr and Co-Cr-Pt ferromagnetic alloys with Co as the main component have been used for the recording layer of hard disks that employ in-plane magnetic recording. In addition, composite materials in which non-magnetic particles such as oxides and carbon are dispersed in Co-Cr-Pt ferromagnetic alloys with Co as the main component are often used for the recording layer of hard disks that employ perpendicular magnetic recording, which has been put to practical use in recent years. Due to the high productivity, magnetic thin films are often produced by sputtering sputtering targets containing the above materials using a magnetron sputtering device.
[0003] In magnetron sputtering equipment, a magnet is placed behind the target, and the magnetic flux leaking from the target surface concentrates plasma near the target to perform sputtering. For this reason, a sputtering target with a large leakage magnetic flux is more efficient at promoting ionization of the inert gas, and a stable discharge can be obtained.
[0004] However, in general, when sputtering a ferromagnetic sputtering target using a magnetron sputtering device, most of the magnetic flux from the magnet passes through the inside of the target, which is a ferromagnetic material, resulting in a problem that the leakage magnetic flux is small and discharge does not occur during sputtering, or the discharge is not stable even if it does occur. In order to solve this problem, it is possible to reduce the content of Co, which is a ferromagnetic metal. However, in this case, the desired magnetic recording film cannot be obtained, so this is not an essential solution. In addition, it is possible to improve the leakage magnetic flux by reducing the thickness of the target, but in this case, the target life is shortened and the target needs to be replaced frequently, which is a factor in increasing costs. Therefore, various technical developments have been made to improve the leakage magnetic flux of sputtering targets.
[0005] Patent Document 1 (Japanese Patent No. 6490589) describes a technology for increasing leakage magnetic flux while containing ferromagnetic metal elements by forming a magnetic phase formed by alloying Pt and Cr with a specific ratio to the ferromagnetic metal element Co, a nonmagnetic phase, and an oxide phase in the target. Specifically, the technology proposes a magnetron sputtering target characterized by having a three-phase structure consisting of (1) a Co-Pt magnetic phase containing Co and Pt, where the ratio of Pt to Co is 4 to 10 atomic %, (2) a Co-Cr-Pt nonmagnetic phase containing Co, Cr, and Pt, where the ratio of Cr to Co is 30 atomic % or more, and (3) an oxide phase containing a metal oxide.
[0006] Patent Document 2 (Japanese Patent No. 4673453) and Patent Document 3 (Japanese Patent No. 5394576) disclose a technique for increasing leakage magnetic flux by adjusting the structural structure of a sputtering target. Specifically, Patent Document 2 proposes a ferromagnetic sputtering target made of a metal with a composition of 20 mol % or less of Cr and the remainder of Co, characterized in that the structural structure of this target comprises a metal base (A) and, in the (A), a spherical phase (B) containing 90 wt % or more of Co and with a difference between the major axis and the minor axis of 0 to 50%. Patent Document 3 proposes a sputtering target made of a metal having a composition of 20 mol % or less of Cr, 5 mol % or more of Pt, and the remainder being Co, characterized in that the target has a metal base (A), and within the (A), a Co-Pt alloy phase (B) containing 40 to 76 mol % of Pt, and a metal or alloy phase (C) different from the phase (B) that is Co or contains Co as a main component.
[0007] On the other hand, non-magnetic materials such as oxides and carbon dispersed in a Co-Cr-Pt ferromagnetic alloy tend to aggregate and segregate. This makes it easy for abnormal discharge to occur during sputtering, and the generation of particles destroyed by the abnormal discharge is also a problem. In order to solve this problem, Patent Document 4 (Patent Publication No. 6317636) proposes an invention that suppresses the generation of microcracks and particles in a sputtering target for magnetic recording media by dispersing an oxide phase containing CrTi2O5 in addition to SiO2 in the metal phase. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 6490589 [Patent Document 2] Patent No. 4673453 [Patent Document 3] Patent No. 5394576 [Patent Document 4] Patent No. 6317636 Summary of the Invention [Problem to be solved by the invention]
[0009] As in Patent Documents 1 to 3, techniques are known for improving the leakage magnetic flux of sputtering targets using Co-Cr-Pt ferromagnetic alloys by modifying the alloy composition or the texture, but these techniques are not effective in preventing the aggregation of non-magnetic materials. Patent Document 4 adds CrTi2O5 to suppress the aggregation of non-magnetic materials, but it is intended for sputtering targets for CoPtCr-SiO2 magnetic recording media and does not provide a solution for sputtering targets that do not require SiO2.
[0010] Therefore, in one embodiment, the present invention aims to provide a Co-Cr-Pt-based sputtering target member that has improved leakage magnetic flux and is also excellent in the effect of suppressing the aggregation of non-magnetic materials, from a viewpoint different from that of the above-mentioned prior art. In another embodiment, the present invention aims to provide a sputtering target assembly including such a sputtering target member. In yet another embodiment, the present invention aims to provide a film formation method using such a sputtering target member. [Means for solving the problem]
[0011] The inventors conducted intensive research to solve the above problems and discovered that by dispersing Co-Cr-Pt alloy particles having a different Co, Cr and Pt content (i.e., different magnetic properties) from that of the matrix phase, which contains Co, Cr, Pt, and a non-magnetic material, in the matrix phase, magnetic non-uniformity is introduced and the leakage magnetic flux of the sputtering target can be increased.
[0012] The inventors also found that the diffusion behavior of the metal components in the sputtering target is slowed down by the matrix phase and the Co-Cr-Pt alloy particles each containing Co, Cr, and Pt. Normally, when the metal components diffuse, non-magnetic materials such as oxides also move, causing aggregation, but this can be reduced and the aggregation of non-magnetic materials can be suppressed.
[0013] The present invention has been completed based on the above findings, and is exemplified below. [1] The alloy has a matrix phase containing Co, Cr, Pt, and a non-magnetic material, and a Co-Cr-Pt alloy particle phase dispersed in the matrix phase, The non-magnetic material contains one or more selected from carbon, oxides, nitrides, and carbides; The Pt content in the Co-Cr-Pt alloy particle phase is 50 to 80 mass %; The mass contents of Co, Cr and Pt in the Co-Cr-Pt alloy particle phase are different from the mass contents of Co, Cr and Pt in the matrix phase, respectively; Sputtering target material. [2] The mass contents (%) of Co, Cr, and Pt in the matrix phase are [Co m ], [Cr m ] and [Pt m ] and the mass contents (%) of Co, Cr, and Pt in the Co-Cr-Pt alloy particle phase are [Co d ], [Cr d ] and [Pt d ], then 15%≦|[Co m ]-[Co d ]|≦41%, 0.4%≦|[Cr m ]-[Cr d ]|≦10%, 40%≦|[Pt m ]-[Pt d ]|≦70%。 [1]. The sputtering target member according to claim 1, wherein | [3] The sputtering target member according to [1] or [2], wherein the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase have an average particle size of 10 to 150 μm. [4] The sputtering target member according to any one of [1] to [3], wherein the non-magnetic material is composed of non-magnetic particles having an average particle size of 0.05 to 5.0 μm. [5] The sputtering target member according to any one of [1] to [4], wherein the mass content of the Co-Cr-Pt alloy particle phase in the sputtering target member is 20 to 45%. [6] The sputtering target member according to any one of [1] to [5], wherein the non-magnetic material contains an oxide. [7] The sputtering target member according to any one of [1] to [6], wherein the matrix phase contains 0.09 to 12 mass % of Cr, 7.5 to 40 mass % of Pt, and 5 to 25 mass % of a non-magnetic material, with the remainder being Co and unavoidable impurities. [8] The sputtering target member according to any one of [1] to [7], wherein the Co-Cr-Pt alloy particle phase contains 1 to 5 mass % of Cr, 50 to 80 mass % of Pt, and the remainder is Co and unavoidable impurities. [9] A sputtering target assembly comprising: the sputtering target member according to any one of [1] to [8]; and a backing tube or a backing plate joined to the sputtering target member.
[10] A film forming method comprising sputtering the sputtering target member according to any one of [1] to [8]. Effect of the Invention
[0014] According to one embodiment of the present invention, it is possible to provide a Co-Cr-Pt sputtering target member that has improved leakage magnetic flux and excellent effects of suppressing aggregation of non-magnetic materials. Therefore, when the sputtering target member is used in a magnetron sputtering device, it is expected that the ionization of the inert gas will be efficiently promoted and stable discharge will be obtained. In addition, since the sputtering target member can be made thick, it is expected to have the advantage of reducing the frequency of replacement and enabling the production of magnetic thin films at low cost. Furthermore, it is expected that the sputtering target is less likely to cause abnormal discharge during sputtering, enabling stable sputtering with fewer particles. [Brief description of the drawings]
[0015] [Figure 1] 1 is an SEM image of a cross-sectional structure of Example 1. [Diagram 2] 2 is an SEM image of a cross-sectional structure of Comparative Example 1. [Diagram 3] 1 is an SEM image of a cross-sectional structure of Comparative Example 9. [Figure 4] 1 is an SEM image of a cross-sectional structure of Comparative Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] (Matrix phase) In one embodiment, the sputtering target member according to the present invention has a matrix phase containing Co, Cr, Pt, and a non-magnetic material. Since the matrix phase contains Co, Cr, Pt, and a non-magnetic material, this sputtering target member is suitable for forming, for example, a recording layer of a perpendicular magnetic recording medium (e.g., hard disk). The composition of the matrix phase can be appropriately set according to the required magnetic properties, but in one embodiment, the matrix phase has a composition containing 0.09 to 12 mass % of Cr, 7.5 to 40 mass % of Pt, and 5 to 25 mass % of a non-magnetic component, with the balance being Co and unavoidable impurities. In a preferred embodiment, the matrix phase has a composition containing 0.09 to 1 mass % of Cr, 10 to 30 mass % of Pt, and 10 to 25 mass % of a non-magnetic component, with the balance being Co and unavoidable impurities. This composition range is required to increase leakage magnetic flux, so there is great significance in adopting the present invention.
[0017] The non-magnetic material contains one or more selected from carbon, oxides, nitrides, and carbides, and typically is substantially composed of one or more selected from carbon, oxides, nitrides, and carbides. It is preferable that the non-magnetic material contains at least an oxide, because it is possible to finely disperse the non-magnetic material in the metal phase using a relatively common grinding and mixing device, and it is more preferable to use only an oxide as the non-magnetic material. Examples of oxides include one or more oxides of elements selected from Si, Al, B, Ba, Be, Ca, Ce, Cr, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr. Among the oxides, SiO2 is preferably added because it has a large effect of contributing to the densification of the sputtering target. Examples of nitrides include one or more nitrides of elements selected from Al, B, Ca, Nb, Si, Ta, Ti, and Zr. Examples of carbides include carbides of one or more elements selected from B, Ca, Nb, Si, Ta, Ti, W, and Zr. The type of non-magnetic material may be appropriately selected depending on the required magnetic properties of the magnetic thin film.
[0018] The Co, Cr, and Pt constituting the matrix phase are composed of fine particles having an average particle size smaller than that of the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase described later. Co, Cr, and Pt may be composed of fine particles, for example, 9 μm or less, but it is difficult to accurately measure the particle size after sintering because diffusion with the Co-Cr-Pt alloy particles progresses during sintering.
[0019] On the other hand, the particle size of the non-magnetic particles constituting the non-magnetic material in the matrix phase can be measured because the particle size is clearly different from that of the metal phase in the structure photograph after sintering. The smaller the particle size of the non-magnetic material, the less likely it is to become the starting point of abnormal discharge. Therefore, the upper limit of the average particle size of the non-magnetic particles constituting the non-magnetic material in the matrix phase is preferably 5.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. If the average particle size of the non-magnetic particles is too small, there is a concern that they will aggregate with each other during the mixed powder preparation process to form lumps (coarse secondary particles), so the lower limit is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. Therefore, in one embodiment, the non-magnetic material is composed of non-magnetic particles with an average particle size of 0.05 to 5.0 μm, and in a preferred embodiment, the non-magnetic material is composed of non-magnetic particles with an average particle size of 0.1 to 2.0 μm.
[0020] In the present invention, the average particle size of the non-magnetic particles constituting the matrix phase is measured by the following method. A cut surface of a surface horizontal to the sputtering surface of the sputtering target member is mirror-polished. On an SEM photograph of the mirror-polished cut surface, which is 450 μm long x 630 μm wide and taken at 200x magnification with a measurement time of 40 seconds per field, the photograph is divided vertically into three equal intervals by two horizontal cutting lines, the cut length of the particle phase of the non-magnetic material cut by each cutting line is measured, and the average cut length (μm) is calculated for each field. The thickness of the cutting line is 1 / 400 of the vertical length of the photograph. This is performed for any 10 fields of view, and the average value of the 10 fields of view is taken as the measured value. Note that the particle phase of the non-magnetic material that is only partially included in the field of view is excluded from the measurement object.
[0021] (Co-Cr-Pt alloy particle phase) In one embodiment, the sputtering target member according to the present invention has a Co-Cr-Pt alloy particle phase dispersed in a matrix phase. The mass content of the Co-Cr-Pt alloy particle phase in the sputtering target member is preferably 20% or more, more preferably 30% or more, and even more preferably 35% or more, because a certain amount of the alloy particle phase is necessary to obtain the effect of increasing leakage magnetic flux. The mass content of the Co-Cr-Pt alloy particle phase in the sputtering target member is preferably 45% or less, more preferably 42% or less, and even more preferably 40% or less, because the aggregation of oxide particles in the matrix phase is prevented.
[0022] In one embodiment, the matrix phase and the Co-Cr-Pt alloy particle phase in the sputtering target member are in a complementary relationship, and the mass content (%) of the matrix phase in the sputtering target member can be expressed as 100 - (mass content (%) of the Co-Cr-Pt alloy particle phase).
[0023] The mass contents of Co, Cr, and Pt in the Co-Cr-Pt alloy particle phase are different from the mass contents of Co, Cr, and Pt in the matrix phase. By dispersing Co-Cr-Pt alloy particles having different contents of Co, Cr, and Pt (i.e., different magnetic properties) from those of the matrix phase in the matrix phase containing Co, Cr, Pt, and a non-magnetic material, magnetic non-uniformity is introduced, and the leakage magnetic flux of the sputtering target can be increased. In addition, since the matrix phase and the Co-Cr-Pt alloy particles each contain Co, Cr, and Pt, the diffusion behavior of the metal components in the sputtering target is gentle. Normally, when the metal components are diffused, non-magnetic materials such as oxides also move, causing aggregation, but this can be reduced, and the aggregation of the non-magnetic materials can be suppressed.
[0024] The mass contents (%) of Co, Cr, and Pt in the matrix phase are [Co m ], [Cr m ] and [Pt m ] and the mass contents (%) of Co, Cr, and Pt in the Co-Cr-Pt alloy particle phase are [Co d ], [Cr d ] and [Pt d ], the absolute value of the difference between the concentration of each component in the matrix phase and the concentration in the Co-Cr-Pt alloy particle phase is |[Co m ]-[Co d ]|,|[Cr m ]-[Cr d ]| and |[Pt m ]-[Pt d A larger |[Co ]| is advantageous in terms of introducing magnetic non-uniformity, but if it is too large, the diffusion behavior becomes large and the aggregation of non-magnetic materials becomes likely. For this reason, the range of 15%≦|[Co m ]-[Co d ]|≦41%, 0.4%≦|[Cr m ]-[Cr d ]|≦10%, 40%≦|[Pt m ]-[Pt d ]|≦70% is preferable, and 20%≦|[Co m ]-[Co d]|≦41%, 1%≦|[Cr m ]-[Cr d ]|≦8%, 40%≦|[Pt m ]-[Pt d ]|≦60% is more preferable, and 30%≦|[Co m ]-[Co d ]|≦41%, 1.5%≦|[Cr m ]-[Cr d ]|≦2%, 40%≦|[Pt m ]-[Pt d It is even more preferable that ]|≦50% holds true.
[0025] If the Pt content in the Co-Cr-Pt alloy particle phase is too low, the effect of preventing the oxidation of Cr contained in the Co-Cr-Pt alloy particles is weakened. Furthermore, by including Pt in the alloy particle phase as much as possible, the ratio of Pt to Co on the matrix side is reduced. This is expected to change the magnetic properties and make the magnetic flux more likely to leak. Therefore, the lower limit of the Pt content in the Co-Cr-Pt alloy particle phase is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more. Furthermore, if the Pt content in the Co-Cr-Pt alloy particle phase is too high, the diffusion of Pt from the alloy particle phase to the matrix phase during sintering is promoted, which causes the occurrence of aggregation. Therefore, the upper limit of the Pt content in the Co-Cr-Pt alloy particle phase is preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less.
[0026] If the Cr content in the Co-Cr-Pt alloy particle phase is too low, the diffusion of Cr from the matrix phase to the alloy particle phase during sintering is promoted. Therefore, the lower limit of the Cr content in the Co-Cr-Pt alloy particle phase is preferably 1 mass% or more, more preferably 1.5 mass% or more, and even more preferably 2 mass% or more. Also, if the Cr content in the Co-Cr-Pt alloy particle phase is too high, the amount of Co-Cr-Pt alloy particles used must be reduced, making it difficult to obtain the effect of improving leakage flux. Therefore, the upper limit of the Cr content in the Co-Cr-Pt alloy particle phase is preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less.
[0027] Therefore, in one embodiment, the Co-Cr-Pt alloy particle phase has a composition containing 1-5 mass% Cr and 50-80 mass% Pt, with the remainder being Co and unavoidable impurities. In a preferred embodiment, the Co-Cr-Pt alloy particle phase has a composition containing 1.5-4 mass% Cr and 60-75 mass% Pt, with the remainder being Co and unavoidable impurities. In a more preferred embodiment, the Co-Cr-Pt alloy particle phase has a composition containing 2-3 mass% Cr and 65-70 mass% Pt, with the remainder being Co and unavoidable impurities.
[0028] The upper limit of the average particle size of the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase is preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 75 μm or less, because if the particle size is too large, it may become the starting point of abnormal discharge during sputtering. The lower limit of the average particle size of the Co-Cr-Pt alloy particles is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, because the smaller the particle size, the larger the specific surface area of the alloy particles becomes, which promotes diffusion with the matrix phase during sintering and reduces the effect of increasing leakage magnetic flux. Therefore, in one embodiment, the Co-Cr-Pt alloy particle phase is composed of Co-Cr-Pt alloy particles having an average particle size of 10 to 150 μm, in a preferred embodiment, the Co-Cr-Pt alloy particle phase is composed of Co-Cr-Pt alloy particles having an average particle size of 20 to 100 μm, and in a more preferred embodiment, the Co-Cr-Pt alloy particle phase is composed of Co-Cr-Pt alloy particles having an average particle size of 30 to 75 μm.
[0029] In the present invention, the average particle size of the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase is measured by the following method. The cut surface of the surface horizontal to the sputtering surface of the sputtering target member is mirror-polished. On an SEM photograph of the mirror-polished cut surface, which is 450 μm long x 630 μm wide and taken at 200 times magnification with a measurement time of 40 seconds per field, the photograph is divided vertically into three equal intervals by two horizontal cutting lines, the cut length of the Co-Cr-Pt alloy particles cut by each cutting line is measured, and the average cut length (μm) is calculated for each field. The thickness of the cutting line is 1 / 400 of the vertical length of the photograph. This is performed for any 10 fields of view, and the average value of the 10 fields of view is taken as the measured value. Co-Cr-Pt alloy particles that are only partially included in the field of view are excluded from the measurement object. In addition, in order to clearly distinguish it from the metal particles that constitute the matrix phase, when determining the average particle size of the Co-Cr-Pt alloy particles, only Co-Cr-Pt alloy particles with a cutting length of 10 μm or more that constitute the Co-Cr-Pt alloy particle phase are used in calculating the average value.
[0030] (Production method) The sputtering target member according to the present invention can be produced by using a powder sintering method, for example, by the following method.
[0031] First, Co powder, Cr powder, and Pt powder are prepared as raw material powders for forming the matrix phase. These metal powders may be prepared by pulverizing a melt-cast ingot, or may be prepared as atomized powder. In addition, powders of non-magnetic materials such as carbon powder, carbide powder, nitride powder, and oxide powder are prepared as raw material powders for forming the matrix phase.
[0032] The purity of the raw material powder for constituting the matrix phase is preferably 90 mol % or more, more preferably 95 mol % or more, and even more preferably 99.9 mol % or more. In a typical embodiment, the raw material powder contains no components other than the indicated components and unavoidable impurities.
[0033] The upper limit of the median diameter (D50) of the raw material powder for constituting the matrix phase is preferably 10 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less, in order to promote fine dispersion during mixing. The lower limit of the median diameter of the raw material powder is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, in order to prevent aggregation due to an increase in specific surface area. The median diameter can be adjusted by pulverization or sieving.
[0034] Next, a Co-Cr-Pt alloy coarse powder is prepared as a raw material powder for forming the Co-Cr-Pt alloy particle phase. The Co-Cr-Pt alloy coarse powder can be prepared by, for example, a gas atomization method. The purity of the raw material powder for forming the Co-Cr-Pt alloy particle phase is preferably 90 mol% or more, more preferably 95 mol% or more, and even more preferably 99.9 mol% or more. In a typical embodiment, the raw material powder does not contain any other than the indicated components and unavoidable impurities.
[0035] The upper limit of the median diameter (D50) of the Co-Cr-Pt alloy coarse powder is preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 75 μm or less, because too large alloy coarse particles can become the starting point of abnormal discharge during sputtering. The lower limit of the median diameter of the Co-Cr-Pt alloy coarse powder is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, because the smaller the particle size, the larger the specific surface area of the alloy coarse particles, which promotes diffusion with the matrix phase during sintering and reduces the effect of increasing leakage magnetic flux. The median diameter can be adjusted by pulverization or sieving.
[0036] Next, the raw powder for forming the matrix phase and the raw powder for forming the Co-Cr-Pt alloy particle phase are weighed to obtain the desired composition, and mixed while being pulverized using a known method such as a ball mill. At this time, care should be taken not to pulverize the Co-Cr-Pt alloy coarse powder excessively. For example, the raw powder for forming the matrix phase is first pulverized and mixed using a ball mill or the like, and then the raw powder for forming the Co-Cr-Pt alloy particle phase is added and pulverized and mixed gently. It is also desirable to seal an inert gas in the pulverization container to suppress oxidation of the raw powder as much as possible. Examples of the inert gas include Ar and N2 gas.
[0037] In the present invention, the median diameter of each raw material powder means the particle size at 50% cumulative volume (D50) in the particle size distribution determined by a laser diffraction / scattering method. In the examples, a particle size distribution measuring device (Model LA-920, manufactured by HORIBA) was used to disperse the powder in an ethanol solvent and measure it. The refractive index used was that of metallic cobalt.
[0038] The mixed powder thus obtained is molded and sintered in a vacuum or inert gas atmosphere by hot pressing. In addition to the hot pressing, various pressure sintering methods such as plasma discharge sintering can be used. In particular, hot isostatic pressing (HIP) is effective for increasing the density of the sintered body, and it is preferable to carry out the hot pressing and hot isostatic pressing in this order from the viewpoint of increasing the density of the sintered body.
[0039] The upper limit of the holding temperature during sintering depends on the composition of the target, but is preferably 1050° C. or lower, more preferably 950° C. or lower, and even more preferably 900° C. or lower, in order to prevent grain growth during sintering. The lower limit of the holding temperature during sintering is preferably 700° C. or higher, more preferably 750° C. or higher, and even more preferably 800° C. or higher, in order to avoid a decrease in density of the sintered body.
[0040] The lower limit of the press pressure during sintering is preferably 20 MPa or more to promote sintering, more preferably 30 MPa or more, and even more preferably 40 MPa or more, and the upper limit of the press pressure during sintering is preferably 100 MPa or less, more preferably 80 MPa or less, and even more preferably 60 MPa or less, taking into account the strength of the die.
[0041] The lower limit of the sintering time is preferably 1 hour or more, more preferably 2 hours or more, and even more preferably 3 hours or more in order to improve the density of the sintered body, and the upper limit of the sintering time is preferably 10 hours or less, more preferably 7 hours or less, and even more preferably 5 hours or less in order to prevent the crystal grains from becoming coarse.
[0042] The resulting sintered body is processed into a desired shape using a lathe or the like to produce a sputtering target member according to one embodiment of the present invention. The target shape is not particularly limited, and examples thereof include a flat plate shape (including a disk shape and a rectangular plate shape) and a cylindrical shape. In one embodiment, the sputtering target member according to the present invention is particularly useful as a sputtering target member used for depositing a granular structure magnetic thin film.
[0043] The sputtering target member may be attached to a substrate such as a backing tube or a backing plate as necessary and mounted in a sputtering apparatus as a sputtering target assembly. The sputtering target member may be mounted in a sputtering apparatus as a sputtering target without using a substrate.
[0044] (Film forming method) In one embodiment, the present invention provides a film forming method including the step of sputtering the above-mentioned sputtering target member. Sputtering conditions can be appropriately set. EXAMPLES
[0045] Examples of the present invention will be described below together with comparative examples. These examples are provided for a better understanding of the present invention and its advantages, and are not intended to limit the present invention.
[0046] (Example 1, Comparative Examples 1, 9, and 11) <1. Preparation of sputtering target components> The following fine powders were prepared as raw powders for forming the matrix phase. All of them are high purity products with a purity of 99.9 mol% or more and contain only the indicated components and unavoidable impurities. The median diameter (D50) of these powders was appropriately adjusted by sieving. Co powder: Median diameter (D50) = 3 μm Cr powder: Median diameter (D50) = 5 μm Pt powder: median diameter (D50) = 1 μm Ru powder: median diameter (D50) = 8 μm B2O3 powder: Median diameter (D50) = 8 μm TiO2 powder: Median diameter (D50) = 0.2 μm SiO2 powder: Median diameter (D50) = 1 μm Cr2O3 powder: Median diameter (D50) = 3 μm CoO powder: median diameter (D50) = 1 μm
[0047] In addition, as the raw material powder for forming the Co-Cr-Pt alloy particle phase, the Co-Cr-Pt alloy coarse powder produced by the gas atomization method was sieved and used. However, in Comparative Example 9, Co coarse powder was used, and in Comparative Example 11, Co-Cr coarse powder was used. The composition and median diameter (D50) of the Co-Cr-Pt alloy coarse powder according to the test number are shown in Table 1. The Co-Cr-Pt alloy coarse powder has a purity of 99.9 mol% or more and contains only Co, Cr, Pt, and unavoidable impurities. It is empirically known that the composition of the Co-Cr-Pt alloy coarse powder is substantially equal to the composition of the Co-Cr-Pt alloy particle phase in the sputtering target.
[0048] Next, each of the raw powders was weighed to have the mass composition described in the column of "raw materials used" in Table 2 according to the test number. Next, the raw powders other than the Co-Cr-Pt alloy coarse powder were enclosed in a ball mill pot with a capacity of 10 liters together with zirconia balls as a grinding medium, and rotated and mixed for 20 hours. The obtained mixed powder and the weighed Co-Cr-Pt alloy coarse powder were put into an automatic mortar and mixed for 2 hours. Next, the obtained mixed powder was filled into a carbon mold, heated to the temperature described in Table 7 in a vacuum atmosphere, and hot pressed under conditions of a holding time of 2 hours and a pressure of 30 MPa to obtain a sintered body. Next, the sintered body removed from the hot press was subjected to hot isostatic pressing (HIP) at the holding temperature and holding time of 2 hours described in Table 7. The pressure was set in the range of 100 to 200 MPa. Furthermore, this was ground using a general-purpose lathe and a surface grinder to obtain a disk-shaped sputtering target member with a diameter of 180 mm and a thickness of 4 mm.
[0049] The composition (mass%) of the matrix phase for each test number calculated from the mixing ratio of the raw material powder is shown in Table 3. The differences in the mass contents of Co, Cr, and Pt in the matrix phase and the Co-Cr-Pt alloy particle phase are shown in Table 4. In addition, the overall composition (mol%, the remainder is Co) of the sputtering target for each test number calculated from the mixing ratio of the raw material powder is shown in Table 5.
[0050] <2. Average particle size of the Co-Cr-Pt alloy particles that compose the Co-Cr-Pt alloy particle phase> For each sputtering target member obtained by the above procedure, the average particle size of the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase dispersed in the matrix phase was determined by the above procedure. The Co-Cr-Pt alloy particle phase was identified using an SEM (Hitachi High-Tech, device name: S-3000N) (Comparative Examples 9 and 11) or an SEM (Hitachi High-Tech, device name: S-3700N) (Example 1 and Comparative Example 1). In consideration of the particle size of the Co-Cr-Pt alloy coarse powder used as the raw material, the coarse particles dispersed in the matrix phase composed of a fine structure were identified as the Co-Cr-Pt alloy particle phase. The observation conditions of the SEM were an acceleration voltage of 15 kV, an irradiation current of 70 μA, an observation magnification of 200 times, and a vertical size of 450 μm x horizontal size of 630 μm (measurement time for one visual field was 40 sec). The results are shown in Table 6.
[0051] 3. Average particle size of non-magnetic particles For each sputtering target member obtained by the above procedure, the average particle size of the non-magnetic particles constituting the matrix phase was determined by the above procedure. The non-magnetic particle phase was identified using an SEM (Hitachi High-Tech, device name: S-3000N) (Comparative Examples 9 and 11) or an SEM (Hitachi High-Tech, device name: S-3700N) (Example 1 and Comparative Example 1). The SEM observation conditions were an acceleration voltage of 15 kV, an irradiation current of 70 μA, an observation magnification of 200 times, and an area of 450 μm long x 630 μm wide (measurement time for one field of view was 40 sec). The results are shown in Table 6.
[0052] <4. Measurement of leakage magnetic flux density (PTF)> For each sputtering target member obtained by the above procedure, leakage magnetic flux was measured in accordance with ASTM F2086-01 (Standard Test Method for Pass Through Flux of Circular Magnetic Sputtering Targets, Method 2). The target was fixed at the center and rotated 0°, 30°, 60°, 90°, and 120° to measure leakage magnetic flux density (PTF). The PTF was divided by the reference field value defined by ASTM and multiplied by 100 to express it as a percentage. The average results for these five points are shown in Table 6 as leakage magnetic flux density (PTF).
[0053] <5. Presence or absence of aggregation of non-magnetic particles around or inside Co-Cr-Pt alloy particles> For each sputtering target member obtained by the above procedure, the presence or absence of agglomeration of non-magnetic particles around or inside the Co-Cr-Pt alloy particles was confirmed by the method described below. A cut surface of the surface parallel to the sputtering surface of the sputtering target was mirror-polished, and an SEM photograph of 450 μm in length and 630 μm in width taken at 200x magnification was prepared. The criteria for judging the presence or absence of agglomeration were as follows. The results are shown in Table 6. With flocculation: (1) The outer circumference of the Co-Cr-Pt alloy particle is covered with a generally continuous non-magnetic particle. "Regularly continuous" means that the particle may be broken in several places, and it is considered that the non-magnetic particle covers 90% or more of the circumference of the Co-Cr-Pt alloy particle (see the structural photograph of Comparative Example 11). (2) 30% or more of the Co-Cr-Pt alloy particles in one field of view contain non-magnetic particles with an equivalent circle diameter of 5 μm or more (see the structural photograph of Comparative Example 9). (3) A Co-Cr-Pt alloy particle is circumscribed by a non-magnetic particle having a diameter of 5 μm or more. No aggregation: If none of the conditions (1) to (3) described under "Occurrence of aggregation" is satisfied, it is determined that no aggregation occurs.
[0054] <6. Consideration> The SEM image of the cross-sectional structure of Example 1 is shown in Fig. 1, the SEM image of the cross-sectional structure of Comparative Example 1 is shown in Fig. 2, the SEM image of the cross-sectional structure of Comparative Example 9 is shown in Fig. 3, and the SEM image of the cross-sectional structure of Comparative Example 11 is shown in Fig. 4. Comparing Example 1 and Comparative Example 1, the overall composition of the sputtering target member is the same in both cases. However, in Example 1, the PTF was improved by dispersing Co-Cr-Pt alloy particles having different contents of Co, Cr, and Pt from those in the matrix phase, which contains Co, Cr, Pt, and a non-magnetic material.
[0055] (Examples 2 to 12, Comparative Examples 2 to 8, 10, and 12) Sputtering targets according to examples and comparative examples that are estimated based on the above findings will be described below. <1. Preparation of sputtering target components> The following fine powders are prepared as raw powders for forming the matrix phase. All of them are high purity products with a purity of 99.9 mol% or more, and contain only the indicated components and unavoidable impurities. The median diameter (D50) of these powders is appropriately adjusted by sieving. Co powder: Median diameter (D50) = 3 μm Cr powder: Median diameter (D50) = 5 μm Pt powder: median diameter (D50) = 1 μm Powder B: Median diameter (D50) = 9 μm Ru powder: median diameter (D50) = 8 μm Ta powder: Median diameter (D50) = 9 μm B2O3 powder: Median diameter (D50) = 8 μm TiO2 powder: Median diameter (D50) = 0.2 μm SiO2 powder: Median diameter (D50) = 1 μm Cr2O3 powder: Median diameter (D50) = 3 μm MnO powder: Median diameter (D50) = 3 μm Ta2O5 powder: Median diameter (D50) = 1 μm CoO powder: median diameter (D50) = 1 μm Co3O4 powder: Median diameter (D50) = 1 μm Si3N4 powder: Median diameter (D50) = 5 μm SiC powder: Median diameter (D50) = 9 μm
[0056] In addition, the Co-Cr-Pt alloy coarse powder produced by gas atomization is used after sieving as the raw material powder for forming the Co-Cr-Pt alloy particle phase. The composition and median diameter (D50) of the Co-Cr-Pt alloy coarse powder according to the test number are shown in Table 1. The purity of the Co-Cr-Pt alloy coarse powder is 99.9 mol% or more, and contains nothing other than Co, Cr, Pt, and unavoidable impurities. It has been empirically found that the composition of the Co-Cr-Pt alloy coarse powder is substantially equal to the composition of the Co-Cr-Pt alloy particle phase in the sputtering target.
[0057] Next, each of the raw material powders is weighed to have the mass composition described in the "raw material used" column of Table 2 according to the test number. Next, the raw material powders other than the Co-Cr-Pt alloy coarse powder are enclosed in a ball mill pot with a capacity of 10 liters together with zirconia balls as a grinding medium, and rotated and mixed for 20 hours. The obtained mixed powder and the weighed Co-Cr-Pt alloy coarse powder are put into an automatic mortar and mixed for 2 hours. Next, the obtained mixed powder is filled into a carbon mold, heated to the temperature described in Table 7 in a vacuum atmosphere, and hot pressed under conditions of a holding time of 2 hours and a pressure of 30 MPa to obtain a sintered body. Next, the sintered body removed from the hot press is subjected to hot isostatic pressing (HIP) at the holding temperature and holding time of 2 hours described in Table 7. The pressure is set in the range of 100 to 200 MPa. Furthermore, this is ground using a general-purpose lathe and a surface grinder to obtain a disk-shaped sputtering target member with a diameter of 180 mm and a thickness of 4 mm.
[0058] The composition (mass%) of the matrix phase for each test number calculated from the mixing ratio of the raw material powder is shown in Table 3. The differences in the mass contents of Co, Cr, and Pt in the matrix phase and the Co-Cr-Pt alloy particle phase are shown in Table 4. In addition, the overall composition (mol%, the remainder is Co) of the sputtering target for each test number calculated from the mixing ratio of the raw material powder is shown in Table 5.
[0059] <2. Average particle size of the Co-Cr-Pt alloy particles that compose the Co-Cr-Pt alloy particle phase> For each sputtering target member obtained by the above procedure, the average particle size of the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase dispersed in the matrix phase is determined by the above procedure. The Co-Cr-Pt alloy particle phase is identified using an SEM (Hitachi High-Tech, device name: S-3700N) (Examples 2 to 12, Comparative Examples 2 to 8, 10, and 12). The observation conditions for the SEM are an acceleration voltage of 15 kV, an irradiation current of 70 μA, an observation magnification of 200 times, and an area of 450 μm long x 630 μm wide (measurement time for one field of view is 40 sec). The results are shown in Table 6.
[0060] 3. Average particle size of non-magnetic particles For each sputtering target member obtained by the above procedure, the average particle size of the non-magnetic particles constituting the matrix phase is determined by the procedure described above. The non-magnetic particle phase is identified using an SEM (Hitachi High-Tech, device name: S-3700N) (Examples 2 to 12, Comparative Examples 2 to 8, 10, and 12). The SEM observation conditions are an acceleration voltage of 15 kV, an irradiation current of 70 μA, an observation magnification of 200 times, and an area of 450 μm long x 630 μm wide (measurement time for one field of view is 40 sec). The results are shown in Table 6.
[0061] <4. Measurement of leakage magnetic flux density (PTF)> For each sputtering target member obtained by the above procedure, the leakage flux is measured in accordance with ASTM F2086-01 (Standard Test Method for Pass Through Flux of Circular Magnetic Sputtering Targets, Method 2). The target is fixed at the center and rotated 0°, 30°, 60°, 90°, and 120° to measure the leakage flux density (PTF). The PTF is divided by the reference field value defined by ASTM and multiplied by 100 to express it as a percentage. The average results for these five points are shown in Table 6 as the leakage flux density (PTF).
[0062] <5. Presence or absence of aggregation of non-magnetic particles around or inside Co-Cr-Pt alloy particles> For each sputtering target member obtained by the above procedure, the presence or absence of agglomeration of non-magnetic particles around or inside the Co-Cr-Pt alloy particles is confirmed by the method described below. A cut surface of the surface parallel to the sputtering surface of the sputtering target is mirror-polished, and an SEM photograph of 450 μm long x 630 μm wide taken at 200x magnification is prepared. The criteria for judging the presence or absence of agglomeration are as follows. The results are shown in Table 6. With flocculation: (1) The outer circumference of the Co-Cr-Pt alloy particle is covered with a generally continuous non-magnetic particle. "Regularly continuous" means that the particle may be broken in several places, and it is considered that the non-magnetic particle covers 90% or more of the circumference of the Co-Cr-Pt alloy particle (see the structural photograph of Comparative Example 11). (2) 30% or more of the Co-Cr-Pt alloy particles in one field of view contain non-magnetic particles with an equivalent circle diameter of 5 μm or more (see the structural photograph of Comparative Example 9). (3) A Co-Cr-Pt alloy particle is circumscribed by a non-magnetic particle having a diameter of 5 μm or more. No aggregation: If none of the conditions (1) to (3) described under "Occurrence of aggregation" is satisfied, it is determined that no aggregation occurs.
[0063] <6. Consideration> Comparing Example 3 and Comparative Example 2, Example 4 and Comparative Example 3, Example 5 and Comparative Example 4, Example 6 and Comparative Example 5, Example 7 and Comparative Example 6, Example 8 and Comparative Example 7, Example 9 and Comparative Example 8, Example 10 and Comparative Example 10, and Example 12 and Comparative Example 12, the overall composition of the sputtering target members is the same. However, the PTF is improved in the examples in which Co-Cr-Pt alloy particles having different contents of Co, Cr and Pt from those of the matrix phase are dispersed in a matrix phase containing Co, Cr, Pt, and a non-magnetic material.
[0064] Comparing Example 2 and Comparative Example 2, the overall composition of the sputtering target member is the same in both cases. In addition, in both Example 2 and Comparative Example 2, coarse Co-Cr-Pt alloy particles having different contents of Co, Cr, and Pt from those in the matrix phase are dispersed in a matrix phase containing Co, Cr, Pt, and a non-magnetic material. However, in Example 2, the composition of the Co-Cr-Pt alloy particle phase (especially the Pt content) is appropriate, so that the PTF is improved compared to Comparative Example 2.
[0065] Comparing Example 11 and Comparative Example 11, the overall composition of the sputtering target member is the same for both. However, the composition of the metal particles dispersed in the matrix phase in Comparative Example 11 is inappropriate. Therefore, the PTF of Example 11 is higher than that of Comparative Example 11. The same can be said when comparing Example 10 and Comparative Example 9.
[0066] [Table 1]
[0067] [Table 2]
[0068] [Table 3]
[0069] [Table 4]
[0070] [Table 5]
[0071] [Table 6]
[0072]
Table 7
Claims
1. The magnetic material has a matrix phase containing Co, Cr, Pt, and a non-magnetic material, and a Co-Cr-Pt alloy particle phase dispersed in the matrix phase, the non-magnetic material contains one or more selected from carbon, oxides, nitrides, and carbides; The Pt content in the Co-Cr-Pt alloy particle phase is 50 to 80 mass %, The mass contents of Co, Cr, and Pt in the Co-Cr-Pt alloy particle phase are different from the mass contents of Co, Cr, and Pt in the matrix phase, respectively; Assuming that the mass contents (%) of Co, Cr and Pt in the matrix phase are [Com], [Cr m] and [Pt m], and the mass contents (%) of Co, Cr and Pt in the Co-Cr-Pt alloy particle phase are [Co d], [Cr d] and [Pt d], respectively, the following relationships are established: 15%≦|[Com]-[Co d]|≦41%, 0.4%≦|[Cr m]-[Cr d]|≦10%, 40%≦|[Pt m]-[Pt d]|≦70%, The mass content of the Co-Cr-Pt alloy grain phase in the sputtering target member is 20 to 45%; Sputtering target material.
2. The mass contents (%) of Co, Cr and Pt in the matrix phase are expressed as [Co m ], [Cr m ] and [Pt m ], and the mass contents (%) of Co, Cr, and Pt in the Co-Cr-Pt alloy particle phase are [Co d ], [Cr d ] and [Pt d ], then 20%≦|[Co m ]-[Co d ]|≦41%, 1%≦|[Cr m ]-[Cr d ]|≦8%, 40%≦|[Pt m ]-[Pt d 2. The sputtering target member according to claim 1, wherein the following relationship holds: |
3. 3. The sputtering target member according to claim 1, wherein the Co-Cr-Pt alloy particles constituting the Co-Cr-Pt alloy particle phase have an average particle size of 10 to 150 μm.
4. 4. The sputtering target member according to claim 1, wherein the non-magnetic material is composed of non-magnetic particles having an average particle size of 0.05 to 5.0 μm.
5. 5. The sputtering target member according to claim 1, wherein the mass content of the Co-Cr-Pt alloy particle phase in the sputtering target member is 30 to 42%.
6. 6. The sputtering target member according to claim 1, wherein the non-magnetic material contains an oxide.
7. 7. The sputtering target member according to claim 1, wherein the matrix phase contains 0.09 to 12 mass % of Cr, 7.5 to 40 mass % of Pt, and 5 to 25 mass % of a nonmagnetic material, with the remainder being Co and unavoidable impurities.
8. The sputtering target member according to any one of claims 1 to 7, wherein the Co-Cr-Pt alloy particle phase contains 1 to 5 mass% Cr, 50 to 80 mass% Pt, and the remainder is composed of Co and unavoidable impurities.
9. A sputtering target assembly comprising the sputtering target member according to any one of claims 1 to 8, and a backing tube or a backing plate joined to the sputtering target member.
10. A film forming method comprising sputtering the sputtering target member according to any one of claims 1 to 8.
Citation Information
Patent Citations
Production of vinyl chloride tile
JP1978094576A
Hydroponic apparatus utilizing roof of car garade
JP1988017636A
Manufacture of ceramic circuit board fired at low temperature
JP1989090589A
Target for magnetron sputtering, and method for manufacturing the same
JP2010255088A
Sputtering target for forming magnetic recording medium film and method for manufacturing the same
JP2011175725A